Diagnosis dan Manajemen Penyakit Ginjal Kronis (PGK) - Vika Kyneissia Gliselda (Yayasan Pendidikan Medika Indonesia, 2021)
Chronic kidney disease (CKD) is a global public health problem with an increasing prevalence and incidence of kidney failure, poor prognosis and high costs. The prevalence of CKD increases with the increasing number of elderly population and the incidence of diabetes mellitus and hypertension. According to the results of the 2010 Global Burden of Disease, CKD was the 27th leading cause of death in the world in 1990 and increased to 18th in 2010. In Indonesia, treatment of kidney disease is the second largest health insurance provider after heart disease. In 2015, the global economic burden related to diabetes was US1.31 trillion, and this is a sizable global economic burden. Chronic kidney disease (CKD) is the 16th leading cause of years of life lost worldwide. Appropriate screening, diagnosis, and management by primary care physicians are: necessary to prevent adverse CKD-related outcomes, including cardiovascular disease, end-stage renal disease, and death. Chronic kidney disease initially does not show signs and symptoms but can progress to kidney failure. Kidney disease can be prevented and managed and the chances of getting effective therapy are greater if caught early.